Influence of vegetative canopy management on the quality of 'Bordô' grape grown in the ‘Planalto Norte Catarinense’ (Revista de Ciências Agroveterinárias, 2024)
In the grapevine, the balance between the fruit load and the adequately lit leaf area influences the quantity and quality of production, making it necessary in some cases to manage the vegetative canopy. In this context, the aim of this work is to evaluate the influence of vegetative canopy management on the quality of the ‘Bordô’ vine, through the following treatments, with the following treatments: T1 - Without leaf removal Management and Without Shoot topping; T2 - Without leaf removal management and with shoot topping; T3 - with leaf removal Management and without shoot topping; T4 - with leaf removal and with shoot topping. The work was carried out in the municipality of Canoinhas - SC, during the 2022/2023 cycle, in a randomized block design, with four replications and ten plants per plot. The berries from T1 had the lowest soluble solids, with a value of 12.9 °Brix, and the highest value for titratable acidity (133.1 meq/L) and the lowest value for pH (3.23). However, it did not differ statistically from the berries from T4 in any of the variables. The absence of pruning and leaf removal + shoot topping did not favor the variables related to maturation. The berries from T2 showed a higher soluble solids content (14.2°Brix) than T1 and T4, lower acidity than T1 and T4 (116.3 meq/L) and pH 3.30. The green pruning favored the quality of the grapes, in comparison with the control and the treatment with leaf removal + shoot topping. The best results were observed for T3, which presented 15.2 °Brix, 108.9 meq/L of acidity and pH of 3.39. It was concluded that the leaf removal at the phenological stage of buckshot berries favors the ripening and quality of grapes.
Keywords: Vitis labrusca L.; maturation; leaf removal; shoot topping